2007
DOI: 10.1038/sj.sc.3102076
|View full text |Cite
|
Sign up to set email alerts
|

The association between regional body composition and metabolic outcomes in athletes with spinal cord injury

Abstract: Study design: Cross-sectional study comparing athletes with spinal cord injury (SCI) and age and body mass index matched able-bodied controls (AB). Objective: To examine the impact of exercise training on the relation between whole body, regional and intermuscular adipose tissue (IMAT) and glucose tolerance, insulin action and lipid profile. Setting: University Research Laboratory, USA. Methods: Fourteen college-aged athletes with SCI (seven men; duration of injury 16.575.7 years, level of injury T5-L5) and 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 27 publications
2
41
1
2
Order By: Relevance
“…Only 3 subjects were assigned to each group, and no control group was included for comparison. There were 12 studies that reported carbohydrate-related outcomes (9,10,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) (Table 1) and 15 that reported lipid-related outcomes (9,10,26,27,30,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) (Table 2). Only 1 study included cardiovascular morbidity as an endpoint (Table 2), and this was assessed using a survey instrument with variable levels of sensitivity and specificity when tested in able-bodied populations (45).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only 3 subjects were assigned to each group, and no control group was included for comparison. There were 12 studies that reported carbohydrate-related outcomes (9,10,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) (Table 1) and 15 that reported lipid-related outcomes (9,10,26,27,30,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) (Table 2). Only 1 study included cardiovascular morbidity as an endpoint (Table 2), and this was assessed using a survey instrument with variable levels of sensitivity and specificity when tested in able-bodied populations (45).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 3 survey studies, one identified a statistically significant inverse correlation (r 5 20.53; P , 0.05) between reported levels of physical activity and fasting serum glucose (9). Another identified an inverse correlation (r 5 20.40) that was not statistically significant (10), whereas the third found no difference in glucose levels between athletes with SCI and a sedentary, able-bodied population (35).…”
Section: Impact Of Exercise Onmentioning
confidence: 98%
See 3 more Smart Citations